Penguatan Akidah Masyarakat Multiagama Di Desa Mondoluku Wringinanom Gresik - Abdulloh Arif Mukhlas; Muhammad Zaenal Abidin; Fitri Indah Sari; Nevia Dina Trianingrum; Najatul Mudzakiroh (PUDAK: Local Wisdom Community Journal, 2022)
Mondoluku Village is a village in Wringinanom District, Gresik Regency, East Java Province. The majority of the people work as turmeric farmers as their daily activities. Turmeric is not a staple food, so every time panin arrives, the panin produce is immediately sold for daily needs. There is no creation yet to produce and market it in powder form, for example, to gain more profit. They live in harmony even with different religions. In mondoluku, Hinduism is a religion followed by their ancestors and forefathers. This religion has existed since the time of the Majapahit kingdom before Islam entered. Since the collapse of Majapahit and the spread of Islam began to develop, things began to turn around. Islam in Mondoluku became the majority religion, even Hinduism was almost destroyed and no longer exists. Until 2012, at first the temple only looked like a gate, now it is starting to grow little by little. In 2022, the temple building looks magnificent, big, with a large yard. This shows the existence of Hindu adherents to bring back past history.